Design of Coal Mine Safety Patrolling System Based on RFID Handhold Terminal - HU Wen-tao; ZHOU Jun; ZHAO Li-chang (Gong-kuang zidonghua, 2010)
In view of problem existed in traditional coal mine safety patrolling method which uses artificial patrolling mode, the paper proposed a design scheme of coal mine safety patrolling system based on RFID handhold terminal. In the scheme, patrolling personnel uses handhold terminal to read his identification card in order to login safety management server to download patrolling tasks and hidden danger database. Then the patrolling personnel reads address identification card at patrolling sites in underground according with the downloaded tasks, detects gas concentration and hidden dangers and makes relative records. When patrolling is finished, the patrolling personnel uploads patrolled data to safety management server. Safety manager statistics and summaries uploaded data, so as to find hidden dangers timely and judges behind schedule according to recorded time. The actual application showed that the system can promote standardization and informatization of coal mine safety patrolling work and can improve safety management level of coal enterprise.